Robust optimization of multi-regional truck scheduling for China-ASEAN cross-border container drayage - Jie He; Zhiming Fang; Xintong Yan; Yuntao Ye; Hao Zhang; Changjian Zhang (Multimodal Transportation)
Container drayage plays an important role in realizing cargo pickup and delivery between container yards and customers. To further describe and optimize the cross-border container drayage between China and the Association of Southeast Asian Nations (ASEAN), this paper studies a multi-regional container drayage problem under travel time uncertainty (MR-CDP-TTU), where multi-regional truck participation and travel time uncertainty are simultaneously considered. We first develop a multi-regional truck scheduling robust optimization model with travel time as the uncertain parameter and the objective of minimizing the total cost. Then, a variable neighborhood tabu search algorithm (VNTSA) is designed by introducing a greedy insertion method to generate the initial solution and structurally combining the tabu search algorithm with the variable neighborhood search algorithm. Finally, comparison and sensitivity analysis is conducted on the cross-border container drayage instances from a China's international logistics company. The results demonstrate that the designed algorithm outperforms in best value, average value, and standard deviation, which indicate that the algorithm can generate quality and stable solutions for the MR-CDP-TTU. Furthermore, the method proposed in this study enables China-ASEAN cross-border logistics to rationally schedule the multi-regional trucks according to their risk attitudes and the maximum deviations of travel time.